Experimental and theoretical 2p core-level spectra of size-selected gas-phase aluminum and silicon cluster cations: chemical shifts, geometric structure, and coordination-dependent screening. Issue 12 (11th March 2019) - Walter, Michael; Vogel, Marlene; Zamudio-Bayer, Vicente; Lindblad, Rebecka; Reichenbach, Thomas; Hirsch, Konstantin; Langenberg, Andreas; Rittmann, Jochen; Kulesza, Alexander; Mitrić, Roland; Moseler, Michael; Möller, Thomas; et al.
Abstract : 2p binding energies of size-selected clusters reveal bonding motifs and help to assign new ground state geometries. Abstract : We present 2p core-level spectra of size-selected aluminum and silicon cluster cations from soft X-ray photoionization efficiency curves and density functional theory. The experimental and theoretical results are in very good quantitative agreement and allow for geometric structure determination. New ground state geometries for Al12 +, Si15 +, Si16 +, and Si19 + are proposed on this basis. The chemical shifts of the 2p electron binding energies reveal a substantial difference for aluminum and silicon clusters: while in aluminum the 2p electron binding energy decreases with increasing coordination number, no such correlation was observed for silicon. The 2p binding energy shifts in clusters of both elements differ strongly from those of the corresponding bulk matter. For aluminum clusters, the core-level shifts between outer shell atoms and the encapsulated atom are of opposite sign and one order of magnitude larger than the corresponding core-level shift between surface and bulk atoms in the solid. For silicon clusters, the core-level shifts are of the same order of magnitude in clusters and in bulk silicon but no obvious correlation of chemical shift and bond length, as present for reconstructed silicon surfaces, are observed.